Philo of Alexandria : an annotated bibliography 1997-2006 with addenda for 1987-1996 - Runia, David T. (Supplements to Vigiliae Christianae, 2012)
This volume, prepared with the collaboration of the International Philo Bibliography Project, is the third in a series of annotated bibliographies on the Jewish exegete and philosopher Philo of Alexandria. It contains a listing of all scholarly writings on Philo for the period 1997 to 2006.